Microglial heterogeneity and complement component 3 elimination within emerging multisensory midbrain compartments during an early critical period - Carroll, Julianne B.; Hamidi, Shaida; Gabriele, Mark L. (Frontiers in Neuroscience, 2023)
The lateral cortex of the inferior colliculus (LCIC) is a midbrain shell region that receives multimodal inputs that target discrete zones of its compartmental (modular-matrix) framework. This arrangement emerges perinatally in mice (postnatal day, P0-P12) as somatosensory and auditory inputs segregate into their respective modular and matrix terminal patterns. Microglial cells (MGCs) perform a variety of critical functions in the developing brain, among them identifying areas of active circuit assembly and selectively pruning exuberant or underutilized connections. Recent evidence in other brain structures suggest considerable MGC heterogeneity across the lifespan, particularly during established developmental critical periods. The present study examines the potential involvement of classical complement cascade signaling (C3-CR3/CD11b) in refining early multisensory networks, and identifies several microglial subsets exhibiting distinct molecular signatures within the nascent LCIC. Immunostaining was performed in GAD67-green fluorescent protein (GFP) and CX3CR1-GFP mice throughout and after the defined LCIC critical period. GAD labeling highlights the emerging LCIC modularity, while CX3CR1 labeling depicts MGCs expressing the fractalkine receptor. C3 expression is widespread throughout the LCIC neuropil early on, prior to its conspicuous absence from modular zones at P8, and more global disappearance following critical period closure. CD11b-expressing microglia while homogeneously distributed at birth, are biased to modular fields at P8 and then the surrounding matrix by P12. Temporal and spatial matching of the disappearance of C3 by LCIC compartment (i.e., modules then matrix) with CD11b-positive MGC occupancy implicates complement signaling in the selective refinement of early LCIC connectivity. Multiple-labeling studies for a variety of established MGC markers (CD11b, CX3CR1, Iba1, TMEM119) indicate significant MGC heterogeneity in the LCIC as its compartments and segregated multisensory maps emerge. Marker colocalization was the exception rather than the rule, suggesting that unique MGC subpopulations exist in the LCIC and perhaps serve distinct developmental roles. Potential mechanisms whereby microglia sculpt early multisensory LCIC maps and how such activity/inactivity may underlie certain neurodevelopmental conditions, including autism spectrum disorder and schizophrenia, are discussed.